2013
DOI: 10.1590/s0100-72032013001000004
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade da assistência pré-natal nos serviços públicos e privados

Abstract: The differences between the services showed that there is a need for actions aiming at the improvement of the prenatal care provided by public services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
1
20

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 15 publications
2
22
1
20
Order By: Relevance
“…The results make up a monitoring for classification of prenatal risk by targeting assistance to achieve the comprehensive care of pregnant women in all its needs. 19, In this study it could be observed the non-request of routine tests to all pregnant women, configured as an unsuitability to PHPN, which recommends their request at the first prenatal visit, as this is an appropriate strategy to prevent, to identify and to correct the abnormalities that can affect the mother and fetus, and institute treatment of existing diseases or that may occur during pregnancy, equating to other studies. 23 In a study on prenatal screening, held in medium-sized municipality in the metropolitan region of São Paulo, some hypotheses were raised to explain the low test coverage in the third trimester: the professionals are used to request the exams only in the first consultation and many fail to ask them again near the thirtieth week of pregnancy and some women fail to take the exams for the second time, although they were requested.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The results make up a monitoring for classification of prenatal risk by targeting assistance to achieve the comprehensive care of pregnant women in all its needs. 19, In this study it could be observed the non-request of routine tests to all pregnant women, configured as an unsuitability to PHPN, which recommends their request at the first prenatal visit, as this is an appropriate strategy to prevent, to identify and to correct the abnormalities that can affect the mother and fetus, and institute treatment of existing diseases or that may occur during pregnancy, equating to other studies. 23 In a study on prenatal screening, held in medium-sized municipality in the metropolitan region of São Paulo, some hypotheses were raised to explain the low test coverage in the third trimester: the professionals are used to request the exams only in the first consultation and many fail to ask them again near the thirtieth week of pregnancy and some women fail to take the exams for the second time, although they were requested.…”
Section: Discussionmentioning
confidence: 98%
“…The main reason for them was no request by health professional. 19 Precisely to weigh the pregnant woman's risk of acquiring unvaccinated disease and transmit during pregnancy, the National Immunization Program (NIP) emphasizes the importance of receiving the vaccine by those against hepatitis B 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As gestantes que frequentam os serviços de atenção pré-natal apresentam número menor de casos de complicações e os fetos, adequado crescimento intrauterino, demonstrando a relação entre assistência pré-natal e o bem-estar do recém-nascido 15 .…”
Section: N T R O D U ç ã Ounclassified
“…O pré-natal abrange uma série de cuidados que buscam a prevenção da saúde da gestante e do recém-nascido, identificando antecipadamente as complicações típicas da gestação incluindo orientações sobre hábitos saudáveis de vida, além de preparar a gestante para o parto e puerpério (4) . No Brasil, a assistência pré-natal de baixo risco, apesar de manter boa cobertura, precisa ser revista, visto que há um baixo cumprimento das ações preconizadas pelo Ministério da Saúde, principalmente quando se refere à captação precoce para a primeira consulta e a frequência às consultas estipuladas (5)(6) . Todas as mulheres necessitam ter acesso ao pré-natal no período da gestação, cuidados diferenciados durante o parto e nas primeiras semanas após o parto (7) .…”
Section: Introductionunclassified